Respon Tanaman Kacang Tanah Terhadap Berbagai Jenis Pupuk Pada Entisols Di Kelurahan Tondo - Karlina Muhsin; Yosep Patadungan; Muhammad Basir (Mitra Sains, 2017)
This study aimed to determine the effect of various kind of fertilizers (biological fertilizer, biological fertilizer + chicken manure, chicken manure, NPK and manure goat) on the growth of peanut plants (Arachis hypogaea L.) in the Entisols soil at Tondo Village. This study was conducted in April to July 2015 in the Tondo Village. This study used a Randomized Block Design (RBD) a factor of 6 (six) treatment using the controls, biological fertilizer, biofertilizer + chicken manure, chicken manure, NPK fertilizer, and manure goat repeated 3 times so that the number of treatment tested a total of 18 plots. Results of this study shows that the use of organic and anorganic fertilizers have an effect on height of peanut plant and number of leaves when compared with controls. Where the provision of all types of organic and inorganic fertilizer (manure goat, NPK fertilizer, chicken manure, combined with the biofertilizer, chicken manure, and fertilizer biological) effect on the height and number of leaves peanuts. These results are consistent with the measurement of the dry weight of seeds, dry weight of brangkasan, P-total soil, total P-Plant and soil microbes. It is also found that biofertilizer combined chicken manure showed the highest performance. In addition, researchers also believe that the use of biological fertilizers and manure have an impact on the environment better because it can improve soil structure over the long term.